(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study aims to discover the implication of social media in the enhancement of marketing communications in Carrefour chain stores in Erbil Province -Iraq. Current years have witnessed the rise of new media channels such as Facebook, YouTube, and Twitter. These platforms allow consumers to take additional active flexible roles as market players and reach almost everyone anywhere and anytime. Also, the new media will put pressure of long established business models and company strategies, but in the same time it will provide plenty opportunities for growth through new adaptive strategies. Social media marketing domain represents a influential instrument for businesses to reach, connect and build strong relationships with their customers. Software package SPSS-20 has been used to analyze the data in order to run statistical tools like average, frequency analysis and chi square. Based on the analysis a conclusion has been drawn that use of social media will enhance marketing communications in Carrefour chain stores in Erbil.